Defining a critical period for inhibitory circuits within the somatosensory cortex - Lo, Shun Qiang (2018)
Although experience-dependent changes in brain inhibitory circuits are thought to play a key role during the “critical period” of brain development, the nature and timing of these changes are poorly understood. We examined the role of sensory experience in sculpting an inhibitory circuit in the primary somatosensory cortex (S1) of mice by using optogenetics to map the connections between parvalbumin (PV) expressing interneurons and layer 2/3 pyramidal cells. Unilateral whisker deprivation decreased the strength and spatial range of inhibitory input provided to pyramidal neurons by PV interneurons in layers 2/3, 4 and 5. By varying the time when sensory input was removed, we determined that the critical period closes around postnatal day 14. This yields the first precise time course of critical period plasticity for an inhibitory circuit.